2022
DOI: 10.1302/0301-620x.104b10.bjj-2022-0201.r2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing two modern total wrist arthroplasties

Abstract: Aims To analyze the short-term outcome of two types of total wrist arthroplasty (TWA) in terms of wrist function, migration, and periprosthetic bone behaviour. Methods A total of 40 patients suffering from non-rheumatoid wrist arthritis were enrolled in a randomized controlled trial comparing the ReMotion and Motec TWAs. Patient-rated and functional outcomes, radiological changes, blood metal ion levels, migration measured by model-based radiostereometric analysis (RSA), bone mineral density (BMD) measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
12
1
1
Order By: Relevance
“…Our study did not see any difference in complication or revision rates with different articulations and, as such, our data do not support the statement by Holm-Glad et al. (2022) that recommended ‘discontinuing the use of MoM in TWA’ in favour of MoP; a statement which was based upon three cases of unclassified osteolysis, presumed but not proved to be the fault of the articulation in a series of 40 MoM implants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study did not see any difference in complication or revision rates with different articulations and, as such, our data do not support the statement by Holm-Glad et al. (2022) that recommended ‘discontinuing the use of MoM in TWA’ in favour of MoP; a statement which was based upon three cases of unclassified osteolysis, presumed but not proved to be the fault of the articulation in a series of 40 MoM implants.…”
Section: Discussioncontrasting
confidence: 99%
“…Our reported complication rate of 19% compares favourably with a large single surgeon study by Reigstad and Rokkum (2018), with a reported 32% complication rate (35 in 110 Motec TWA). Our rates also compare well with a more recent randomized controlled trial comparing Motec TWA with another implant that had complication rates of 35% and revision rates of 15% for the Motec group (Holm-Glad et al., 2022). A systematic review of TWA complications found a 31% complication rate in arthroplasty cases over a range of generations and devices, though this complication rate dropped to 13% in later fourth-generation models (Berber et al., 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The search yielded 1858 results. After screening and full-text review, 12 studies met the inclusion criteria (Figure 1) (Badge et al., 2016; Boeckstyns et al., 2013; Brinkhorst et al., 2018; Ferreres et al., 2011; Harlingen et al., 2011; Holm-Glad et al., 2022; Holzbauer et al., 2022; Honecker et al., 2019; Matsui et al., 2020; Reigstad et al., 2012, 2017; Rossello et al., 2022). Reigstad et al.…”
Section: Resultsmentioning
confidence: 99%
“…Online Figure S1 show the ROB scores for the included studies. There were five prospective studies, six retrospective studies and one RCT (note that the series by Holm-Glad et al. (2022) was an RCT, but the comparison arms were two different TWA implants; therefore, this was included and analysed as a prospective study using ROBINS-1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation